Isolation and characterization of cadmium-resistant Bacillus cereus strains from Cd-contaminated mining areas for potential bioremediation applications - Liang, Bixia; Feng, Yimeng; Ji, Xiyue; Li, Chune; Li, Qian; Zeng, Zhenshun; Wang, Yuqi (Frontiers in Microbiology, 2025)
Cadmium (Cd) is a naturally occurring heavy metal found in the soil. However, its concentrations can be substantially increased by anthropogenic activities, presenting considerable environmental challenges. One effective remediation strategy is soil bioremediation, which employs indigenous bacteria to mitigate contamination. This study aimed to identify Cd-resistant bacteria and assess their potential for bioremediating Cd-contaminated soil. Two Cd-resistant bacterial strains, designated C9 and C27, were isolated from Cd-contaminated soil at concentrations ranging from 100 to 500 mg/L. Morphological analysis and 16S rDNA sequencing identified both strains as Bacillus cereus. The strains’ capacity to adsorb and remove Cd from solutions was assessed, as well as their resistance to other heavy metals, including Zinc (Zn) and Thallium (Tl). Optimal Cd adsorption was observed at 36 h for strain C9 and at 48 h for strain C27, with maximum removal rates achieved at a Cd concentration of 70 μM. Both strains demonstrated substantial resistance to heavy metals in the order Zn > Cd > Tl on solid media. Additionally, they exhibited strong salt tolerance, starch hydrolysis, citrate utilization, and ammonia production capabilities. Notably, both strains produced significantly higher levels of siderophores compared to the model bacterium Bacillus subtilis 3,610, with strain C9 exhibiting superior siderophore production. This enhanced siderophore activity is hypothesized to contribute to Cd resistance. Collectively, these findings suggest that strains C9 and C27 have significant potential for the bioremediation of Cd-contaminated environments. Future research will focus on elucidating the molecular mechanisms underlying heavy-metal resistance and optimizing their application in large-scale bioremediation strategies.